2023
DOI: 10.3390/land12101883
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Preference of Public Art Design in Urban Landscapes: Evidence from an Event-Related Potential Study

Yue Cheng,
Jiayin Chen,
Jiahua Li
et al.

Abstract: As urbanization quickens, the role of public art in urban landscape design gains prominence. Nevertheless, how stylistic characteristics of landscape public art affect aesthetic preferences remains insufficiently discussed, particularly with objective assessment methods. The use of event-related potential (ERP) can offer neurophysiological evidence to support research and practice in landscape art design. We employed a 2 (artistic features) × 2 (professional proficiency) repeated-measures design, involving abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…Studies show that stimuli-matching cognitive states can elicit positive responses [51,52]. Furthermore, the amplitude of P200 significantly increases in response to positive or beneficial stimuli [32,53]. As demonstrated by Guo et al [54] on preferences for robot appearances, the results indicated a significantly increased P200 amplitude in individuals' responses to preferred robots compared to nonpreferred ones.…”
Section: Event-related Potential-based Methods For Perceptual Evaluationmentioning
confidence: 79%
See 2 more Smart Citations
“…Studies show that stimuli-matching cognitive states can elicit positive responses [51,52]. Furthermore, the amplitude of P200 significantly increases in response to positive or beneficial stimuli [32,53]. As demonstrated by Guo et al [54] on preferences for robot appearances, the results indicated a significantly increased P200 amplitude in individuals' responses to preferred robots compared to nonpreferred ones.…”
Section: Event-related Potential-based Methods For Perceptual Evaluationmentioning
confidence: 79%
“…The advantage of these methods is their ability to collect rich data from a wide range of samples; however, these methods have limitations, such as the inability to capture participants' emotional responses in real time, which may lead to discrepancies between reported experiences and actual feelings [30,31]. Additionally, traditional data collection may be influenced by participants' environments and willingness, with cognitive processing often occurring unconsciously or during distraction, which direct interviews may not fully reveal [32].…”
Section: Previous Research Methods and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation